2022
DOI: 10.1038/s41598-022-13610-6
|View full text |Cite
|
Sign up to set email alerts
|

miR-375 is cold exposure sensitive and drives thermogenesis in visceral adipose tissue derived stem cells

Abstract: Activation of brown adipose tissue may increase energy expenditure by non-shivering thermogenesis. Cold exposure is one of the options to activate brown adipocytes. To link changes in energy metabolism with microRNA expression (miRNAs), we analyzed 158 miRNAs in serum of 169 healthy individuals before and after cold exposure. Validating the results of a miRNA array, a significant down-regulation of miR-375 after cold exposure (P < 0.0001) was detected. These changes went along with a significant negative co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Seeliger et al . 49 demonstrated that miR-375 knockdown during visceral preadipocyte differentiation upregulated the adipogenesis marker genes ADIPOQ and ADIPOR2 . Gezginci-Oktayoglu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Seeliger et al . 49 demonstrated that miR-375 knockdown during visceral preadipocyte differentiation upregulated the adipogenesis marker genes ADIPOQ and ADIPOR2 . Gezginci-Oktayoglu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, miR‐375, which has an anti‐oncogene activity, was suggested as a candidate tumour suppressor 43 . Recently, our group could identify a connection between circulating miR‐375 levels and response to cold exposure 44 . Furthermore, miR‐375 may drive thermogenesis in visceral adipose tissue derived stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…43 Recently, our group could identify a connection between circulating miR-375 levels and response to cold exposure. 44 Furthermore, miR-375 may drive thermogenesis in visceral adipose tissue derived stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR-375 in 3T3-L1 cells enhanced adipocyte differentiation by reducing ERK1/2 phosphorylation and increased the mRNA expression of key differentiation transcription factors (CEBPα and PPARγ) and aP2, which results in triglyceride accumulation. Seeliger et al [31] demonstrated that miR-375 knockdown during visceral preadipocyte differentiation upregulated the adipogenesis marker genes ADIPOQ and ADIPOR2. Gezginci-Oktayoglu et al ( 2020) reported that reducing miR-375 expression improved Erk1 expression in ARIP cells, and suppression of miR-375 suppressed the expression of the adipogenesis markers PPAR2, LPL, GLUT4, and leptin.…”
Section: Discussionmentioning
confidence: 99%
“…Species Target Regulation Function of Gene Mus musculus [30] CEBPα Up Transcription factor that directly promotes expression of the adipogenic genes PPARγ Up Cooperative induction of adipogenesis with CEBPα FABP4 Up Fatty acid uptake and transport for storage as triglycerides in lipid droplets Homo sapiens [31,32] ADIPOQ Down Adiponectin hormone, regulates blood glucose levels and promotes the degradation of fatty acids…”
Section: Table 2 Regulation Of Gene Expression By Mir-375 In Differen...mentioning
confidence: 99%